PERMIAN TETRAPOD FOOTPRINTS: BIOSTRATIGRAPHY AND BIOCHRONOLOGY - Lucas S.G.; Hunt A.P. (My University, 2006)
Permian tetrapod footprints are known from localities in North America, South America, Europe and Africa. These footprints comprise four ichnofacies, the Chelichnus ichnofacies from aeolianites and the Batrachichnus, Brontopodus and Characichnos ichnofacies from water-laid (mostly red-bed) strata. Permian track assemblages of the Chelichnus ichnofacies are of uniform ichnogeneric composition and low diversity, range in age from Early to Late Permian, and thus are of no biostratigraphic significance. Footprints of the Batrachichnus and Brontopodus ichnofacies represent two biostratigraphically distinct assemblages: (1) Early Permian assemblages characterized by Amphisauropus, Batrachichnus, Dimetropus, Dromopus, Hyloidichnus, Limnopus and Varanopus; and (2) Middle to Late Permian assemblages characterized by Brontopus, Dicynodontipus, Lunaepes, Pachypes, Planipes, and/or Rhynchosauroides. Few Permian footprint assemblages are demonstrably of Middle Permian (Guadalupian) age, and there is a global gap in the footprint record equivalent to at least Roadian time. Permian tetrapod footprints represent only two biostratigraphically distinct assemblages, an Early Permian pelycosaur assemblage and a Middle to Late Permian therapsid assemblage. Therefore, footprints provide a global Permian biochronology of only two time intervals, much less than the ten time intervals that can be distinguished with tetrapod body fossils. © The Geological Society of London.
Keywords: Guadalupian; Paleozoic::Permian::Guadalupian; Палеозой::Пермская::Гваделупский